"Home Is Where Your Root Is": Place Making, Belonging, and Community Building among Somalis in Chicago. Issue 2 (11th April 2021) - Magan, Ifrah Mahamud; Padgett, Deborah K
Abstract: This qualitative study examines the notion of home as it relates to place making, belonging, and community building. Using a phenomenological method of inquiry, data were gathered through in-depth qualitative interviews with 15 Somali Americans and subjected to transcendental phenomenological analyses. Three major themes were found: (1) the meaning of community: being Somali and Muslim; (2) "We help each other. We are connected"; and (3) "Home is where your root is." The study findings highlight how Somali participants drew on their faith and culture as foundational to community building and drew on acts of mutual giving and receiving to bind them together even as subjective feelings of "home" could be place based or could transcend geography. Although sometimes disrupted by bias and discrimination, Somalis persevered in defining themselves and pursuing a sense of belonging both within their own community and in the city at large. This study offers an expansive and dynamic view of the meaning of place making, community building, and belonging (home) in the lives of displaced refugees. Both research and practice can benefit from special attention given to the "natural" formation of refugee communities and their role in enhancing adjustment to life in a new land.